At play in Belfast : children's folklore and identities in Northern Ireland - Lanclos, Donna M., 1970- (Rutgers series in childhood studies., 2003)
Writing about children on the school playgrounds of working-class Belfast, Northern Ireland, Donna M. Lanclos uses their own words to show how they shape their social identities. She explores their ideas about gender, family, adult-child interactions, and Protestant/Catholic tensions.